FORMS AND STATUS OF PHOSPHORUS IN ACID SOILS OF CID SOILS OF IMPHAL WEST DISTRICT, MANIPUR (INDIA - LINTHOI WATHAM; HEROJIT SINGH ATHOKPAM; K. NANDINI DEVI, NANDINI CHONGTHAM; NAOREM BRAJENDRA SINGH; N. GOPIMOHAN SINGH (The Bioscan, 2018)
The phosphorus fractions of the twenty surface soils (0 -15 cm) of Imphal West district, Manipur and their relationship with some physico-chemical properties of the soils were studied. A significant relationship was obtained between organic-P and total-P in the soils. The average Sal-P, Fe-P, Al-P, Red-P, Occl-P and Ca-P content were 8.70, 73.38, 50.83, 82.54, 29.00 and 22.17 ppm, respectively. The inorganic P fractions in the soils were in the order: Red-P > Fe-P > Al-P > Occl-P > Ca-P > Sal-P. Sal-P had a significant correlation with E.C. (r = 0.661**) and C.E.C. (r = 0.455*). Fe-P had a negative correlation with soil pH(r = -0.565*) and positively correlated with O.C. (r = 0.502*). Al-P had a negatively correlated with soil pH(r = 0.510*) and positively correlated with O.C. (r = 0.698**), available N (r = 0.508**) and C.E.C. (r =0.699**). Red-P had a significant correlation with C.E.C. (r = 0.555*) and negatively correlated with silt (r = -0.455*). Occl-P had a significant negative correlation with silt content of the soil (r = - 0.530*) and positively correlated with C.E.C. (r = 0.577 **). Ca-P had a positive correlation with E.C. (r = 0.539 *), clay (r = 0.583**) and C.E.C. (r = 0.605 **) and negative correlation with sand (r = -0.500 *). Among the different fractions Sal-P, Red-P and Occl-P was positively and significantly correlated with Ca-P (r = 0.534*), (r = 0.583**) and (r = 0.534*), respectively and negatively correlated with Org-P (r = -0.563*) and sal-P. Al-P was positively and significantly correlated with Red-P (0.506*).